Ali je 5% EMLA učinkovita pri zmanjševanju bolečine ob venepunkciji pri otroku v primerjavi z nefarmakološkimi ukrepi? - Oštir, Majda (Slovenska pediatrija, 2010)
Pain is a common experience for hospitalized children. Venipuncture is recognised as one of the most painful and most frequent invasive procedures performed by nurses. Despite mounting research on treatment of acute procedure-related pain, it remains inadequately treated. Topical anaesthetics such as EMLA can provide reliable superficial anaesthesia for decreasing pain caused by venipuncture, insertion of intravenous cannulae, immunizations and lumbar puncture. Non-pharmacological techniques encompass a wide array of modalities, such as hypnosis, listening to music, and distraction. Those too are known to be effective in decreasing pain in similar interventions. The aimof this literature review was to look for evidence that EMLA is more effective in decreasing pain in venipuncture in children than the technique ofdistraction. Conclusions: In this literature review there was strong evidence that routinely performed procedure-related pain, such as venipuncturein children, can be effectively reduced through the use of EMLA cream .There is no evidence that non-pharmacological techniques are more effective than EMLA cream, but there is evidence that distraction and hypnosisare effective in reducing pain at venipuncture in children
Keywords: Administration, Topical; Anestetiki lokalni; Anesthetics, Local; Bolečina; Child; Flebotomija; lokalna anestezija; otroci; Otrok; Pain; Phlebotomy; Zdravilo, lokalna uporaba